Preoperative neutrophil-lymphocyte ratio predicts the risk of microvascular invasion in hepatocellular carcinoma: A meta-analysis. Issue 3 (September 2019) - Zeng, Furong; Chen, Bin; Zeng, Jiling; Wang, Zhiming; Xiao, Liang; Deng, Guangtong
Background: Preoperative estimation of microvascular invasion is of great significance for the clinical decision making in hepatocellular carcinoma. Neutrophil-lymphocyte ratio (NLR) has been reported to be correlated with the poor prognosis of hepatocellular carcinoma. However, the conclusions are conflicting on whether high preoperative NLR level is associated with the presence of microvascular invasion. Aim: To evaluate the association between preoperative NLR level and the risk of microvascular invasion in hepatocellular carcinoma. Methods: Relevant studies were identified by searching PubMed and Embase through February 2019. Fixed or random models were applied to analyze the data based on the heterogeneity. Subgroup, sensitivity, and publication bias analyses were performed. Review Manager 5.3 and STATA software were used for the meta-analysis. Results: A total of 15 studies were eventually included in this meta-analysis. Pooled data based on retrospective cohort studies showed there are more hepatocellular carcinoma patients with vascular invasion (OR 1.74; 95% Cl 1.42, 2.12; P < 0.001) and microvascular invasion (OR 1.62 95% Cl 1.39, 1.89; P < 0.001) in the high NLR group than in the low NLR group. Of case-control studies, a higher preoperative NLR level was found in the microvascular invasion positive group than in the microvascular invasion negative group (OR 0.62; 95% Cl 0.35, 0.90; P < 0.001). The subgroup, sensitivity, and publication bias analyses did not change the results. Conclusion: A higher preoperative NLR level is positively correlated with the risk of microvascular invasion in hepatocellular carcinoma.